An Implementation Model of Sustainability Reporting in Village-Owned Enterprise and Small and Medium Enterprise - Kurniawan, Putu Sukma (Indonesian Journal of Sustainability Accounting and Management, 2018)
This article describes the implementation model of sustainability reporting in village-owned enterprise (VOE) and small and medium enterprises (SMEs), especially in Indonesia. This research design is a qualitative descriptive study and literature research. This research was conducted at the village-owned enterprise and some small and medium enterprise in Tajun village, Buleleng, Bali. The process of this research is divided into initial research, data collection, create the sustainability reporting model, and the implementation of the sustainability reporting model. The methods of collected data are semi-structured interview, observation, and document analysis. Sustainability reporting model in village-owned enterprise and small and medium enterprises based on GRI G4 standard. There are five stages on sustainability reporting model for VOE and SMEs. The five stages are prepare stage, connect stage, define stage, monitoring stage, and reporting stage. Sustainability reporting on VOE and SMEs increases transparency towards stakeholders and improves the optimization of business process. This result indicated that VOE and SMEs can more contribute than other related business in sustainability context. The impact of this research can help more VOE and SMEs reach and build their sustainability in their business activities.